The Influence of Digital Advertising and Content Marketing on Increasing Sales of MSME Products on Instagram - Agus Setiawan; Sarwani Sarwani; Fedianty Augustinah; Liling Listyawati (LPPM STIE Kasih Bangsa, 2025)
This study examines the causal relationship between online promotion strategies and the distribution of digital marketing materials with increased sales of MSMEs on Instagram. The background is changes in consumer behavior and developments in digital technology that have encouraged MSMEs to adapt to social media marketing. Using quantitative methods with an explanatory research design and purposive sampling techniques, 96 respondents who had purchased MSME products through Instagram were ob-tained. Data analysis included validity tests, reliability tests, classical assumptions, multiple linear regression, t-tests, F-tests, and determination coefficients. The results indicate that digital ads and marketing content have a positive and significant impact, both partially and simultaneously, on sales growth. Based on the test results, the digital advertising variable was proven to have a positive and significant influence on sales growth, as indicated by a t-value of 3.843, which exceeded the critical value of 1.661 with a significance level of 0.000 < 0.05. The marketing content variable also has a positive and significant impact, reflected in the t-value of 7.559 > 1.661 and Sig. 0.000 < 0.05. Simultaneously, both variables positively and significantly influence sales growth, as evidenced by the calculated F value of 249.092 with a significance level of 0.000 < 0.05. Simultaneously, both variables positively and significantly influence sales growth, as evidenced by the calculated F value of 249.092 with a significance level of 0.000 < 0.05. In conclusion, the integration and consistent use of these two strategies can improve the sales performance of MSMEs and their competi-tiveness in the digital market.